Pemodelan Sistem Dinamik Mitigasi Banjir Untuk Mengurangi Luas Sawah Terdampak Banjir Di Jawa Timur: A System Thinking Approach - Riski, Raulia; Anisa Dzulkarnain; Adzanil Rachmadhi Putra; Julieta Arneysa Nixieshakira; Siti Nur Fadhilah; Yanuar Cahyo Eko Wahana (Fountain of Informatics Journal, 2024)
Abstrak Indonesia merupakan salah satu negara Agraris terbesar di dunia, yang artinya sebagian besar penduduk Negara Indonesia bekerja di sektor pertanian, termasuk di Jawa Timur. Salah satu media databooks juga mencatatkan bahwa Jawa Timur adalah provinsi dengan luas lahan pertanian seluas 1.7 hektare. Namun sayangnya, Jawa Timur juga tercatat sebagai daerah yang sering terjadi banjir. Dimana tercatat sejumlah 211 kasus banjir yang melanda Jawa Timur pada tahun 2022. Beberapa kasus banjir yang terjadi juga mempengaruhi rasio jumlah lahan pertanian produktif yang ada di area Jawa Timur. Penelitian ini mengadopsi metode System Dynamic untuk mengidentifikasi faktor aktor-faktor yang mempengaruhi banjir, terutama pada sektor pertanian, kemudian mengidentifikasi penanganan dan pencegahan banjir tersebut untuk mengurangi jumlah sawah yang terdampak. Penelitian ini merupakan penelitian deskriptif kualitatif dengan sumber data primer maupun sekunder dari website pemerintah maupun jurnal terdahulu. Penelitian ini disajikan dalam bentuk analisis diagram kausatik mengenai mitigasi banjir pada sektor pertanian di Jawa Timur. Hasil penelitian menunjukkan ada tujuh submodel yang saling mempengaruhi dalam sistem mitigasi bencana banjir dalam penelitian ini, yaitu economic vulnerability, physical vulnerability, flood vulnerability, social vulnerability, adaptive capacity, flood risk, dan flood hazard. Kata kunci: mitigasi bencana banjir, sawah, sistem dinamik, pemodelan, diagram kausatik   Abstract [System Dynamics Model of Flood Mitigation to Reduce the Flood-Affected Rice Fields Area in East Java: A System Thinking Approach] Indonesia is one of the largest agricultural countries in the world, which means that the majority of the Indonesian population works in the agricultural sector, including in East Java. One of the media databooks also noted that East Java is a province with an agricultural land area of 1.7 hectares. However, unfortunately, East Java is also listed as an area that frequently experiences flooding. A total of 211 cases of flooding were recorded that hit East Java in 2022. Several cases of flooding that occurred also affected the ratio of the amount of productive agricultural land in the East Java area. This research adopts the System Dynamic method to identify the factors that influence flooding, especially in the agricultural sector, then identify the handling and prevention of flooding to reduce the number of affected rice fields. This research is a qualitative descriptive study with primary and secondary data sources from government websites and previous journals. This research is presented in the form of a causal diagram analysis regarding flood mitigation in the agricultural sector in East Java. The research results show that there are seven sub-models that influence each other in the flood disaster mitigation system in this research, namely economic vulnerability, physical vulnerability, flood vulnerability, social vulnerability, adaptive capacity, flood risk, and flood hazard. Keywords: flood mitigation, rice field, system dynamics, modeling, causal diagram